The Future Of Sustainable Agriculture: A Review Of Iot And Autonomous Control In Vertical Hydroponic Farming - Mohd Azmi K.H.; Mohamed Radzi N.A.; Ahmad A. (VSB-Technical University of Ostrava, 2025)
By 2050, the global population is expected to exceed 9.7 billion, increasing the demand for food production. Vertical hydroponic (VHF) systems, which enable hydroponically growing plants in space-constrained situations emerge as a promising solution to these difficulties. To address the limitations of traditional farming methods and the challenges faced in VHF, such as manual monitoring and inefficient resource utilization, this survey paper examines how IoT and ACS are integrated into VHF to enhance crop management. It discusses the advantages of this integration, including real-time monitoring, automation, and improved environmental control. Examples of IoT-ACS implementations in VHF, such as automated nutrient dosing systems and real-time root monitoring, are provided to illustrate the diverse applications of these technologies. This paper also presents the challenges such as connectivity issues and sensor calibration must be addressed for successful implementation. Finally, this article demonstrates how IoT and ACS have the potential to change agriculture and handle the growing demand for food production in a sustainable manner. ? 2024 ADVANCES IN ELECTRICAL AND ELECTRONIC ENGINEERING.